MUS81 cleaves TOP1-derived lesions and other DNA-protein cross-links - Marini, Victoria; Nikulenkov, Fedor; Samadder, Pounami; Juul, Sissel; Knudsen, Birgitta R; Krejci, Lumir (BMC biology, 2023)
BACKGROUND: DNA-protein cross-links (DPCs) are one of the most deleterious DNA lesions, originating from various sources, including enzymatic activity. For instance, topoisomerases, which play a fundamental role in DNA metabolic processes such as replication and transcription, can be trapped and remain covalently bound to DNA in the presence of poisons or nearby DNA damage. Given the complexity of individual DPCs, numerous repair pathways have been described. The protein tyrosyl-DNA phosphodiesterase 1 (Tdp1) has been demonstrated to be responsible for removing topoisomerase 1 (Top1). Nevertheless, studies in budding yeast have indicated that alternative pathways involving Mus81, a structure-specific DNA endonuclease, could also remove Top1 and other DPCs. RESULTS: This study shows that MUS81 can efficiently cleave various DNA substrates modified by fluorescein, streptavidin or proteolytically processed topoisomerase. Furthermore, the inability of MUS81 to cleave substrates bearing native TOP1 suggests that TOP1 must be either dislodged or partially degraded prior to MUS81 cleavage. We demonstrated that MUS81 could cleave a model DPC in nuclear extracts and that depletion of TDP1 in MUS81-KO cells induces sensitivity to the TOP1 poison camptothecin (CPT) and affects cell proliferation. This sensitivity is only partially suppressed by TOP1 depletion, indicating that other DPCs might require the MUS81 activity for cell proliferation. CONCLUSIONS: Our data indicate that MUS81 and TDP1 play independent roles in the repair of CPT-induced lesions, thus representing new therapeutic targets for cancer cell sensitisation in combination with TOP1 inhibitors.
Keywords: DNA vazebné proteiny; oprava DNA; Saccharomyces cerevisiae; fosfodiesterasy; Endonucleases; DNA Damage; poškození DNA; Saccharomyces cerevisiae - proteiny; Saccharomyces cerevisiae Proteins; DNA-topoisomerasy I; endonukleasy; DNA Topoisomerases, Type I; DNA Repair; Phosphoric Diester Hydrolases; DNA-Binding Proteins